2020
DOI: 10.21873/anticanres.14234
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Liver Transplant Patient-derived Tumor Xenograft (PDX) Model Using Cryopreserved Pancreatic Ductal Adenocarcinoma

Abstract: Background/Aim: There is rapid progression and widespread use of patient-derived tumor xenografts (PDX) in translational pancreatic cancer research. This study aimed to establish a liver transplant PDX model using cryopreserved primary pancreatic ductal adenocarcinoma (PDAC). Patients and Methods: Primary PDAC from 10 patients were cryopreserved and transplanted into immunodeficient mice using the liver pocket method. H&E staining and immunohistochemical staining, such as p53, Smad4, and MUC1 were used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…ExiTron nano 12000 is a nanoparticle-based, non-iodinated contrast agent that provides both liver and spleen CT contrast (17). Previous reports revealed that mouse liver tumors can be identified by CT using ExiTron nano 12000 in pre-clinical translational research (17,(24)(25)(26). ExiTron nano 12000 subsequently has been used for CECT imaging of lymph node metastasis in a lung cancer model in rat (27).…”
Section: Discussionmentioning
confidence: 99%
“…ExiTron nano 12000 is a nanoparticle-based, non-iodinated contrast agent that provides both liver and spleen CT contrast (17). Previous reports revealed that mouse liver tumors can be identified by CT using ExiTron nano 12000 in pre-clinical translational research (17,(24)(25)(26). ExiTron nano 12000 subsequently has been used for CECT imaging of lymph node metastasis in a lung cancer model in rat (27).…”
Section: Discussionmentioning
confidence: 99%
“…Using HE-stained slides, two experimenters evaluated the histopathological features of adenocarcinoma with comparisons between original tumors and xenografted tumors. Immunohistochemical analysis of Ki67 was performed using rabbit Ki67 (1:400; Cell Signaling Technology, Danvers, MA, USA) on paraffin-embedded sections to measure cell proliferative capacity 28 . Five fields of tumor tissues from a single specimen were arbitrarily photographed at 400 × magnification.…”
Section: Methodsmentioning
confidence: 99%
“…PDAC PDX mouse models have been improved and/or expanded in a variety of ways. Cryopreserved PDAC was introduced into liver to generate a robust model of PDAC liver metastasis of tumors from 6 of 10 patient donors in one third of recipient mice (110). Another means of advancing PDX models was deriving cancer from a tissue source other than primary tumor.…”
Section: Pdx Technical Advancementsmentioning
confidence: 99%